2015
DOI: 10.1007/s00128-015-1505-9
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effect of Silver and Platinum Nanoparticles Toward the Freshwater Microalga Pseudokirchneriella subcapitata

Abstract: The growing use of nanoparticles in a wide range of products has resulted in their release into the aquatic environment; therefore, an understanding of the toxic effects of nanoparticles on aquatic organisms is of permanent importance. The aim of this study was to evaluate the toxicity of silver and platinum nanoparticles toward the freshwater microalga, Pseudokirchneriella subcapitata. Algal growth and photosynthetic pigments were determined to quantitate the effects of varying concentrations of Ag and Pt nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 16 publications
(17 reference statements)
1
26
0
Order By: Relevance
“…In another study by Oukarroum et al [29], it was shown that temperature increases the noxious consequences of Ag NPs on aquatic alga. Total inhibition of algal growth of the freshwater microalga Pseudokirchneriella subcapitata was caused by Ag NPs at 5 mg L −1 [30]. He et al [31] found that the toxicity of Ag was mainly due to silver ions.…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Oukarroum et al [29], it was shown that temperature increases the noxious consequences of Ag NPs on aquatic alga. Total inhibition of algal growth of the freshwater microalga Pseudokirchneriella subcapitata was caused by Ag NPs at 5 mg L −1 [30]. He et al [31] found that the toxicity of Ag was mainly due to silver ions.…”
Section: Introductionmentioning
confidence: 99%
“…We then used a range of nanoscale concentrations (1–20 mg/L) related to expected or recorded environmental concentrations [ 39 , 71 73 ] to assess the biological effect of the NPs on C. reinhardtii using endpoints such as algal growth, membrane integrity, Chl fluorescence photosystem II efficiency and oxidative stress. Our results revealed two distinct groupings: Au and Pt NPs having little or no effect on the alga, and Ag, Pd and CuO NPs displaying a strong effect on almost all endpoints (Additional file 1 : Table S6).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, there has been only limited knowledge about the toxicity of Pt NPs on algae. For example, Pt NPs decreased growth rate, and Chl fluorescence and oxidative stress on P. subcapitata and C. reinhardtii [ 39 , 40 ]. The latter authors also suggested that the toxicity of Pt NPs might be only partly attributed to dissolved form of Pt in the case of P. subcapitata and that also the shading effect might influence toxicity [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approaches based on monitoring the biological effects rather than detecting and quantifying pollutants are needed. Several studies have tried to focus on the possible adverse effects in terms of cytotoxicity and genotoxicity of nanoparticles in living organisms, both animals (Aye et al, 2013;Peng et al, 2013;Tang et al, 2013) and plants (Bandyopadhyay et al, 2015;Moon et al, 2014;Rico et al, 2015) including, recently, marine organisms (Blickley et al, 2014;Książyk et al, 2015;Mackevica et al, 2015;Tang et al, 2014). Indeed, an increasing input of nanoparticles in the aquatic environment is expected, especially in riverine and coastal areas (Corsi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%